2013
DOI: 10.1002/prep.201300042
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies of Pressure Sensitization of Zirconium Carbide and Zirconium Silicate on Burning Rates in a RDX‐AP based Composite Propellant

Abstract: In a systematic study to compare the effects of the values of burning rate and pressure exponent in RDX‐AP based composite propellant, various compositions with varying percentages of zirconium carbide (ZrC) and zirconium silicate (ZrSiO4) were formulated to select a suitable candidate. Various rocket parameters of each formulation were theoretically predicted by the NASA CEC‐71 program and the burning rate was evaluated in pressure range of 3–11 MPa. In addition, density, sensitivity, and thermal properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Ammonium Perchlorate (AP) is widely used in composite propellants (CP), [1][2][3][4][5][6] composite modied double-based propellants (CMDBP) [7][8][9][10] and fuel air explosives (FAE) 11,12 as an excellent oxidizer. The studies have shown that the burning rate of propellants and the brisance of FAE are enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…Ammonium Perchlorate (AP) is widely used in composite propellants (CP), [1][2][3][4][5][6] composite modied double-based propellants (CMDBP) [7][8][9][10] and fuel air explosives (FAE) 11,12 as an excellent oxidizer. The studies have shown that the burning rate of propellants and the brisance of FAE are enhanced.…”
Section: Introductionmentioning
confidence: 99%